PELATIHAN TEKNIK DAN PRODUKSI SIARAN DIGITAL DENGAN VLOG DAN RADIO STREAMING MEDIA ONLINE PADA YAYASAN MEDIA KASIH TANGERANG - Tarsani; Gora, Radita; Dwijayanti, Risqi Inayah (Jurnal Pengabdian Masyarakat Satya Widyakarya, 2023)
Not many orphanages provide proper skills training or effectively showcase the potential of their children to the public. Limited resources and lack of exposure often hinder the children's ability to grow and acquire knowledge beyond their environment. At the Media Kasih Foundation in Tangerang, the children are interested in expressing themselves through social media and digital broadcasting. However, they lack adequate skills, especially in public speaking and audio-visual content production. To address this, the Community Service Team from the Faculty of Social and Political Sciences (FISIP) at Satya Negara Indonesia University (USNI) conducted a training program on digital broadcasting, vlogging, and online radio streaming. The program targets teenagers at junior high, senior high, and college levels, focusing on basic digital production techniques and the creation of creative, educational content. The outcome is video and audio content uploaded to platforms like YouTube and social radio apps such as Spoon.